The joint-limits and singularity avoidance in robotic welding - Huo, Liguo; Baron, Luc (Industrial robot, 2008)
Purpose - The aim of this paper is to develop a redundancy-resolution (RR) algorithm to optimize the joint space trajectory of the six-rotation-axis industrial robot as performing arc-welding tasks.Design methodology approach - The rotation of the tool around its symmetry axis is clearly irrelevant to the view of the task to be accomplished besides some exceptional situations. When performed with a general 6-degrees-of-freedom (DOF) manipulator, there exists one DOF of redundancy that remains. By taking advantage of the symmetry axis of the welding electrode, the authors decompose the required instantaneous twist of the electrode into two orthogonal components, one lying into the relevant task subspace and one into the redundant task subspace, respectively. Joint-limits and singularity avoidance are considered as the optimization objectives.Findings - The twist-decomposition algorithm is able to optimize effectively the joint space trajectory. It has been tested and demonstrated in simulation.Originality value - A new RR algorithm is introduced for the six-rotation-axis industrial robot performing welding tasks. A new kinetostatic performance index is proposed on evaluating the kinematic quality of robotic postures. It can also be used in other applications like milling, deburing and many other tasks requiring less than 6-DOF in tool frame.